INVESTIGATION OF CHEMICAL COMPOSITION OF GIANTS IN THE HYADES - Shereta, E. P. (Одеські астрономічні публікації, 2009)
This paper has presented the results of abundance analysis of three giants in the Hyades. The study based on the spectra which were obtained on 1.93 telescope of the Haute-Provence Observatory (France) equipped ELODIE spectrometer, spectral resolution is 40 000, in the spectral range of 4400 – 6800 АА, the main parameters - the effective temperature Teff, the surface gravity lg g, microturbulent velocity Vt and elemental abundances of Fe, Na, Mg, Al, Si, Ca, Ti, V, Cr, Co, Ni were determined. The determination errors were presented. The studied stars shown the homogeneity of chemical composition and Na overabundance.